ANOLIS SEX CHROMOSOMES ARE DERIVED FROM A SINGLE ANCESTRAL PAIR. (23rd December 2013) - Gamble, Tony; Geneva, Anthony J.; Glor, Richard E.; Zarkower, David
<x xml:space="preserve">Abstract</x> To explain the frequency and distribution of heteromorphic sex chromosomes in the lizard genus Anolis, we compared the relative roles of sex chromosome conservation versus turnover of sex‐determining mechanisms. We used model‐based comparative methods to reconstruct karyotype evolution and the presence of heteromorphic sex chromosomes onto a newly generated Anolis phylogeny. We found that heteromorphic sex chromosomes evolved multiple times in the genus. Fluorescent in situ hybridization (FISH) of repetitive DNA showed variable rates of Y chromosome degeneration among Anolis species and identified previously undetected, homomorphic sex chromosomes in two species. We confirmed homology of sex chromosomes in the genus by performing FISH of an X‐linked bacterial artificial chromosome (BAC) and quantitative PCR of X‐linked genes in multiple Anolis species sampled across the phylogeny. Taken together, these results are consistent with long‐term conservation of sex chromosomes in the group. Our results pave the way to address additional questions related to Anolis sex chromosome evolution and describe a conceptual framework that can be used to evaluate the origins and evolution of heteromorphic sex chromosomes in other clades.